Recent advances in nanotheranostics for triple negative breast cancer treatment - Vikram Thakur (Journal of Experimental & Clinical Cancer Research, 2019)
Abstract Triple-negative breast cancer (TNBC) is the most complex and aggressive type of breast cancer encountered world widely in women. Absence of hormonal receptors on breast cancer cells necessitates the chemotherapy as the only treatment regime. High propensity to metastasize and relapse in addition to poor prognosis and survival motivated the oncologist, nano-medical scientist to develop novel and efficient nanotherapies to solve such a big TNBC challenge. Recently, the focus for enhanced availability, targeted cellular uptake with minimal toxicity is achieved by nano-carriers. These smart nano-carriers carrying all the necessary arsenals (drugs, tracking probe, and ligand) designed in such a way that specifically targets the TNBC cells at site. Articulating the targeted delivery system with multifunctional molecules for high specificity, tracking, diagnosis, and treatment emerged as theranostic approach. In this review, in addition to classical treatment modalities, recent advances in nanotheranostics for early and effective diagnostic and treatment is discussed. This review highlighted the recently FDA approved immunotherapy and all the ongoing clinical trials for TNBC, in addition to nanoparticle assisted immunotherapy. Futuristic but realistic advancements in artificial intelligence (AI) and machine learning not only improve early diagnosis but also assist clinicians for their workup in TNBC. The novel concept of Nanoparticles induced endothelial leakiness (NanoEL) as a way of tumor invasion is also discussed in addition to classical EPR effect. This review intends to provide basic insight and understanding of the novel nano-therapeutic modalities in TNBC diagnosis and treatment and to sensitize the readers for continue designing the novel nanomedicine. This is the first time that designing nanoparticles with stoichiometric definable number of antibodies per nanoparticle now represents the next level of precision by design in nanomedicine.